DESKRIPSI KEPUASAN MAHASISWA SEBAGAI KONSUMEN TERHADAP LAYANAN PENDIDIKAN PADA UNIVERSITAS â€œXâ€ DI SURABAYA - Nurahaju, Rini; Widanti, Nurul Sih (Universitas Pendidikan Mandalika, 2022)
Abstract: Education is a service industry that provides services to students in need. The community's need for education has prompted many educational institutions to be established, including from the private sector. The number of universities makes the need for each university to be able to provide the best service for the community, especially for students as consumers. The increasingly fierce competition with universities that open similar study programs both in the state and private sector, increases the urgency of evaluating and improving the quality of education in its services to students. Students are the main customers of the educational process in higher education. Thus, services in a university must be oriented to student satisfaction. Student satisfaction is a situation where students feel a balance between what they expect, namely the cost (cost) they spend to get or return the goods or services they want (return of investment). This research was conducted at the University of